2011
DOI: 10.1158/0008-5472.can-11-1745
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Mouse Model of Von Hippel–Lindau Kidney Disease Leading to Renal Cancers by Expression of a Constitutively Active Mutant of HIF1α

Abstract: Renal cancers are highly aggressive and clinically challenging, but a transgenic mouse model to promote pathologic studies and therapeutic advances has yet to be established. Here we report the generation of a transgenic mouse model of von Hippel-Lindau (VHL) renal cancer termed the TRACK model (transgenic cancer of the kidney). TRACK mice specifically express a mutated, constitutively active HIF1α in kidney proximal tubule (PT) cells. Kidney histologies displayed by TRACK mice are highly similar to histologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 48 publications
10
114
0
Order By: Relevance
“…In addition, there is evidence that overexpression of HIF-1␣ in the renal proximal tubules is sufficient to induce tumors (17), collectively suggesting that the aggressive phenotype associated with HIF-2 may be acquired irrespective of the VHL status and that HIF-1 also serves a tumorigenic role depending on the cellular background. Therefore, we repeated experiments using A498 cells reconstituted with the mouse VHL homologue (A498/Vhlh) and the Caki-1 RCC cell line harboring normal VHL status and a dominant pattern of HIF-1␣ expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is evidence that overexpression of HIF-1␣ in the renal proximal tubules is sufficient to induce tumors (17), collectively suggesting that the aggressive phenotype associated with HIF-2 may be acquired irrespective of the VHL status and that HIF-1 also serves a tumorigenic role depending on the cellular background. Therefore, we repeated experiments using A498 cells reconstituted with the mouse VHL homologue (A498/Vhlh) and the Caki-1 RCC cell line harboring normal VHL status and a dominant pattern of HIF-1␣ expression.…”
Section: Resultsmentioning
confidence: 99%
“…In view of abundant evidence linking certain types of cysts to defects in primary cilia, it has been suggested that the microtubule stabilization function of VHL is key to its role in suppressing cysts (66). Several mouse models in which the VHL gene has been inactivated develop various cysts (although not SCAs) (67)(68)(69)(70), suggesting fertile avenues for future research on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic inactivation of VHL is an early event in most ccRCCs, but deletion of Vhl in renal epithelial cells in mice does not cause tumor formation (5 (25,(46)(47)(48). Vhl/Trp53 deletion leads to the formation of simple and atypical renal cysts, renal tumors as well as carcinomas in other organs of the genital tract (8).…”
Section: Discussionmentioning
confidence: 99%
“…These studies argue that whereas HIF2a activity is tumor promoting, there is a selection against HIF1a expression or activity during the progression of some cases of ccRCC. On the other hand, because HIF1a is strongly expressed in single and multicellular clusters of VHL-null cells and in cystic lesions in VHL patients (4), and because transgenic overexpression of HIF1a in mouse proximal tubular epithelial cells causes a clear cell appearance, increased proliferation, and a disorganized tubular morphology (25), and because many human ccRCCs express HIF1a and HIF1a target genes (26), it may also be argued that HIF1a plays an important role in promoting ccRCC development. These studies have largely focused on fully transformed, genetically complex ccRCC cell lines derived from advanced tumors, and it remains unclear if and how HIF1a and HIF2a contribute to the earliest stages of initiation of ccRCC.…”
Section: Introductionmentioning
confidence: 99%